Modulation of Electrical Conductivity and Lattice Distortions in Bulk HVPE-Grown GaN. (1st January 2019) - Wolff, Niklas; Jordt, Philipp; Braniste, Tudor; Popa, Veaceslav; Monaico, Eduard; Ursaki, Veaceslav; Petraru, Adrian; Adelung, Rainer; Murphy, Bridget M.; Kienle, Lorenz; Tiginyanu, Ion
Abstract : The nature of self-organized three-dimensional structured architectures with spatially modulated electrical conductivity emerging in the process of hydride vapor phase epitaxial growth of single crystalline n-GaN wafers is revealed by photoelectrochemical etching. The amplitude of the carrier concentration modulation throughout the sample is derived from photoluminescence analysis and the localized heterogeneous piezoelectric response is demonstrated. The formation of such architectures is rationalized based on the generation of V-shaped pits and their subsequent overgrowth in variable direction. Detailed structure analysis with respect to X-ray diffraction and transmission electron microscopy gives striking evidence for inelastic strain to manifest in distortions of the P63 mc wurtzite-type structure. The deviation from hexagonal symmetry by angular distortions of the β angle between the basal plane and c-axis is found to be of around 1°. It is concluded that the lattice distortions are generated by the misfit strains originating during crystal growth, which are slightly relaxed upon photoelectrochemical etching.